A new species of Centris (Paracentris) Cameron, 1903 from northeastern Brazil, with a key for the Centris species of the Caatinga region (Hymenoptera: Apidae) - Vivallo, Felipe; Zanella, Fernando César Vieira (Zootaxa, 2012)
Centris (Paracentris) Cameron is one of the subgenera with the greatest species richness of the bee tribe Centridini. Inthis paper, Centris nordestina, a new Brazilian species of the subgenus is described, and due to its close relationship witha clade of Andean species, a new biogeographical track is defined uniting northeastern Brazil with the Andes. For the first time a key for the species of the Caatinga region, the semiarid region of northeastern Brazil, is provided.